Herbicide application techniques - Dixit, Anil (Indian Farming, 2018)
Herbicides are the most effective and economical tool in weed management. They are applied as pre-plant soil incorporation, preemergence and post-emergence. Selection of a herbicide depends upon weed flora (broad leaved, sedges, grasses etc.) and time of application (before or after planting). Single herbicide can not control all weeds. Hence, tank-mix or sequential application of herbicides is needed for broad-spectrum weed control. Knapsack sprayer fitted with flat-fan nozzleor flood jet (cut nozzle) nozzle is recommended for application of herbicides. Proper calibration of sprayers, appropriate herbicide, dose and time of application, and proper precautions during and after spraying is required for safe and effective use of herbicides.